Factors correlated to attempted suicide - Hesketh, José Luiz; Castro, Archimedes Guimarães de (Revista de Saúde Pública, 1978)
The objective of this paper is to present a discriptive study of attempted suicides admitted at the Emergency Room of the Hospital de Sobradinho, in the Federal District (Brazil), during the year of 1976. The total sample included 22 males and 105 females, with ages varying from 13 to 51 years, with income up to about one minimal wage (about 80 dolars), performing semiqualified or unqualified jobs, living in the towns of Sobradinho and Planaltina (mostly). The procedure consisted of the codification of the data obtained through unstructured psyquiatric interviews done individually with the subjects soon after they had been cared for at the Emergency Room or during their stay at the Hospital. The folowing hypotheses were confirmed: (1)the attempt is more frequent among people younger than 25; (2) the attempt is more frequent among women; (3)there is an interaction between sex and age in determining the suicide attempt; (4)suicide women show more affective problems than suicide men; (5)suicide men show more socio-economic problems than suicide women; (6)male attempts are more intentional. The following hypotheses were rejected: (1)suicide attempt is more frequent among people older than 55(the study shows that this limit is around 40); (2)attempts are more frequent among people with previous attempts; (3)the attempt is more frequent among people with psychological problems.